One-Step Urethroplasty in Recurrent Chordee on Scrotal Hipospadia - Muhammad Jailani (Britain International for Academic Research (BIAR) Publisher, 2020)
Hypospadia is genitalia externa congenital anomaly in male. Recurrent chordee is one of most complication often happen in hypospadias correction. One-step urethroplasty in recurrent chordee is very challenging due to formed massive fibrosis. Correction surgery goals is to release chordee and moving meatus urethra externa to glans tip, and could be done by one-step or two-step. We report patient, 13 years old boy came with chief complain urinate from scrotal region. Patient was diagnose with scrotal hypospadia. Patient done chordee excision previously, but penis still not straight. Then, we perform one-step urethroplasty rechordee excision with local flap. Patient was follow-up one week postoperative, wound in good condition, and dehiscent wasn’t found. Urinary catheter released after three weeks. Evaluation also done in one month postoperative, and found no fistel. One-step urethroplasty rechordee excision was perform in scrotal hypospadi with local urethroplasty flap technique. Evaluation from beginning until two months postoperative found no fistel and urinate in straight line.